Dimensionamento de reservatórios pluviais através de curvas adimensionais - Possenti, Gabriel (2018)
There is a duality to which water is currently subjected. Despite being known countless uses for this resource, for many times it doesn’t get the attention and care it demands. The development of great civilizations has always been connected to water, also showing its economic value. By this and other factors the world has been, as the years goes by, paying more attention to the imminent lack of it, seeking methods to save and preserve water. It is in this scenario that the use of reservoirs rises with strength, as one of the most effective ways to preserve water, bringing along economy from the financial perspective and other benefits such as aid in flood control. Reservoirs are, primarily, an investment. If it’s propagation is desired it is necessary that they become as effective as possible. This thesis makes use of the main factors that influence the size of a reservoir (existing demand, capitation area, reliability e characteristic rain), condensing them in a dimensionless curve which aims to improve accuracy and facilitate the choice of reservoir volumes for Toledo – PR region. As a way of hem the obtained results, a comparison is made between the tested method and the methods suggested by NBR 15527:2007, that deals with the use of coverages in urban areas for non-potable purposes.